Law Enforcement of State Jurisdiction in Hacking Crimes - Nurkhasanah, Kharisma Ika; Prasetyo, Zydane Maheswara (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
Along with the development of information and communication technology, apart from having a positive impact with ease of communication and transactions, there are also negative impacts such as the emergence of crimes in cyberspace or cybercrime. Law enforcement regarding various types of cyber crime turns out to be problematic in practice, especially regarding purchasing problems. This research aims to determine and analyze law enforcement and secret regulations for hacking crimes as well as legal policies regarding the implementation of cyber law in hacking crimes in Indonesia. The author employs a statutory approach and a conceptual approach as part of a normative juridical research methodology. This research results show that cyber crime fraud is regulated in Article 2 of the ITE Law which applies the principle of extra-territorial fraud. Indonesia can implement this through international cooperation which includes extradition, mutual legal assistance, and collaboration between law enforcers. Handling problems that occur internationally and nationally related to cross-border activities and extraterritorial consequences, is carried out with a global approach in a universal regulatory mechanism, there may be a single legal framework and depends on regional mechanisms and on national legal systems that provide effective handling of digital threats.